Pengembangan Kedai Rumah Madinah Dalam Menentukan Strategi Bersaing - Yosep, Charles; Suci, Rahayu Puji; Handini, Dharmayanti Pri (Bulletin of Management and Business, 2020)
Madinah Malang in the future using the IFAS Matrix, EFAS Matrix, SWOT Matrix, I-E Matrix, SWOT Matrix and QSPM Matrix. Quantitative method. Research settings at the Madinah Malang Restaurant. The results showed that the ability of Malang Medina Restaurant Shops with IFAS and EFAS were able to exploit their weaknesses. At the decision making stage with QSPM, the alternative strategy chosen was the Market Development Strategy at the Madinah Malang Restaurant Shop. This strategy has a TAS score of 6,595. Limitations / Implications for research need to increase Promotion by utilizing existing technology through mass media such as: Instagram, Facebook, Google.